2020
DOI: 10.1021/acsomega.0c00227
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Dependent Competitive Electroreduction of CO2 into CO and Formate on Cu(111) from an Improved H Coverage-Dependent Electrochemical Model with Explicit Solvent Effect

Abstract: An improved density functional theory-based H coverage-dependent electrochemical model with explicit solvent effect is proposed for Cu (111), which is used to identify potential-dependent initial competitive CO 2 electroreduction pathways considering HER. We find that a chemisorbed CO 2 molecule at the present electrode/aqueous interface can be spontaneously formed and the overpotentials can affect its coordination pattern. The Eley−Rideal mechanism may be more favorable during the initial CO 2 electroreductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The CO 2 electroreduction has two two‐electron‐transfer products, that is, CO and formate (HCOO − ). [ 59,60 ] After the initial CO 2 activation and CO 2 •− radical formation, [ 61 ] the configuration of CO 2 •− on the catalyst surface determines the reaction pathway. The adsorption through strong metalcarbon bonds or metal–carbon/metal–oxygen bonds can generate carboxyl (*COOH) intermediate, the precursor of CO, after electron and proton transfer.…”
Section: Co2 Electroreduction Mechanisms On Cu Catalystsmentioning
confidence: 99%
“…The CO 2 electroreduction has two two‐electron‐transfer products, that is, CO and formate (HCOO − ). [ 59,60 ] After the initial CO 2 activation and CO 2 •− radical formation, [ 61 ] the configuration of CO 2 •− on the catalyst surface determines the reaction pathway. The adsorption through strong metalcarbon bonds or metal–carbon/metal–oxygen bonds can generate carboxyl (*COOH) intermediate, the precursor of CO, after electron and proton transfer.…”
Section: Co2 Electroreduction Mechanisms On Cu Catalystsmentioning
confidence: 99%
“…−1.35 and −0.90 eV for CO 2 electroreduction into CH 4 and CH 3 OH product at clean Cu(111)/H 2 O interface, which both are notably less negative than those of Br − modified Cu(111)/H 2 O interface. 36,45 Additionally, the reaction free energy for CO 2 electroreduction into CH 4 and CH 3 OH product at I − modified Cu(111)/H 2 O interface is also significantly more negative than that of clean Cu(111)/H 2 O interface (ca. −2.60 and −1.40 eV vs. −0.90 eV).…”
Section: Effect Of Br − and I − On Production Pathways Of C 1 Productmentioning
confidence: 99%
“…13 Further supporting these conclusions is the more recent study in which the authors concluded that on Cu(111) “the Eley–Rideal reaction via proton-electron transfer may be more favorable during initial CO 2 electroreduction into CO through intermediate COOH, whereas chemisorbed CO 2 reacting with a surface-adsorbed H into HCOO − via Langmuir–Hinshelwood mechanical is more facile to occur ”. 14 Importantly, HCOO − is kinetically favored (lower transition state energies) over CO formation.…”
Section: Introductionmentioning
confidence: 99%